Cultural and commercial exchanges between the Orient and Greek world : Athens, Greece, 25-28 October 1990 (Εθνικό Ίδρυμα Ερευνών. Κέντρο Νεοελληνικών Ερευνών, 1991)
This one-day seminar has been arranged by the Centre for Neohellenic Research of the National Hellenic Research Foundation in response to an invitation from the Greek Government to participate in and help to organize the events planned for the three-day visit of the "ship of peace", the Fulk-al-Salamah, kindly lent by the Sultan of Oman. The object of the seminar is to provide a forum where Greek scholars can meet their foreign counterparts and representatives of the media who have put to sea on this peaceable mission which is part of the programme entitled "Silk Roads: Roads of Dialogue". The "Silk Roads" programme, arranged under the auspices of the World Decade for Cultural Development, is something more than a pure research project: one of its principal aims is to reopen the dialogue between the peoples of the world in the hope that, by drawing on their historical memories and acknowledging the importance of cultural interaction, they will re-establish communication and mutual understanding. [...] (From the publisher)